2020
DOI: 10.1074/jbc.ac120.015720
|View full text |Cite|
|
Sign up to set email alerts
|

Template-dependent inhibition of coronavirus RNA-dependent RNA polymerase by remdesivir reveals a second mechanism of action

Abstract: Remdesivir (RDV) is a direct-acting antiviral agent that is used to treat patients with severe coronavirus disease 2019 (COVID-19). RDV targets the viral RNA-dependent RNA polymerase (RdRp) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We have previously shown that incorporation of the active triphosphate form of RDV (RDV-TP) at position i causes delayed chain-termination at position i+3. Here we demonstrate that the S861G mutation in RdRp eliminates chain-termination, which confirms the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
208
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(222 citation statements)
references
References 32 publications
12
208
2
Order By: Relevance
“…Our model provides a structural basis for stalling of RdRp after incorporation of the fourth RMP. This is in agreement with previous studies that have demonstrated that mutations of nsp12(Ser861) reduce the inhibitory effect of remdesivir (Gordon et al, 2020; Tchesnokov et al, 2020). Our structure also shows that the cyano group of each of the four RMP molecules is readily accommodated at the active site, with no apparent steric interactions with the enzyme.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our model provides a structural basis for stalling of RdRp after incorporation of the fourth RMP. This is in agreement with previous studies that have demonstrated that mutations of nsp12(Ser861) reduce the inhibitory effect of remdesivir (Gordon et al, 2020; Tchesnokov et al, 2020). Our structure also shows that the cyano group of each of the four RMP molecules is readily accommodated at the active site, with no apparent steric interactions with the enzyme.…”
Section: Resultssupporting
confidence: 93%
“…Initial structural studies with a single copy of RMP in positions −1 (Wang et al, 2020b) and +1 (Yin et al, 2020) demonstrate that RMP is able to be incorporated into the nascent transcript through Watson-Crick base pairing with template strand uracil bases. However, together with previous studies (Gordon et al, 2020; Tchesnokov et al, 2020), our structure and kinetic data show that incorporation of RMP at neither of these positions results in RdRp inhibition. Another recent study (Kokic, 2020) determined multiple structures of RdRp in complex with synthetic substrates in which RMP had been incorporated at specific positions.…”
Section: Discussionsupporting
confidence: 84%
“…Compound 3j (Remdesivir) is a promising candidate based on existing evidence, and clinical trials of remdesivir are now underway among adults with COVID-19 in hospitals (NIH 2020 ). Remdesivir is a direct-acting antiviral agent used for the treatment of serious 2019 coronavirus disease (COVID-19) patients (Tchesnokov et al 2020 ; Baby et al 2020 ). It showed a mixed outcome with a reasonable side effect in COVID-19 patients (Singh et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patient sequences all belonged to clade 20B, corresponding to lineage B.1.1. According to literature data, [18][19][20][21][22][23][24][25] no mutations related to possible resistance to remdesivir were observed, also as minority variant when considering a cut off of 1%.…”
Section: Case Historymentioning
confidence: 97%